2013
DOI: 10.1063/1.4858638
|View full text |Cite
|
Sign up to set email alerts
|

OSLD energy response performance and dose accuracy at 24 - 1250 keV: Comparison with TLD-100H and TLD-100

Abstract: Abstract. OSLD was evaluated in terms of energy response and accuracy of the measured dose in comparison with TLD-100H and TLD-100. The OSLD showed a better energy response performance for H p (10) whereas for H p (0.07), TLD-100H is superior than the others. The OSLD dose accuracy is comparable with the other two dosimeters since it fulfilled the requirement of the ICRP trumpet graph analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…The experimental results obtained in this study are in good agreement with another published results (Kadir et al 2013;Luo & Rotunda 2006). It can be seen from Figure 6 that the phenomena of under-response and overresponse were exhibited by both the simulated values and experimental results.…”
Section: Simulation Based On a Published Worksupporting
confidence: 91%
“…The experimental results obtained in this study are in good agreement with another published results (Kadir et al 2013;Luo & Rotunda 2006). It can be seen from Figure 6 that the phenomena of under-response and overresponse were exhibited by both the simulated values and experimental results.…”
Section: Simulation Based On a Published Worksupporting
confidence: 91%
“…This was also supported by Kouakou et al, who evaluated dosimetric performance and uncertainty for TLD-100, and reported that a proportion of TL chips were unable to measure accurately at 0.1-10mGy (19). A study by Kadir et al investigated the uncertainty associated with the energy response of TLD-100 to an ideal dose, which had a maximum deviation of 125.04% for Hp (0.07) against 45.22% for Hp (10) at 24keV, with the shallow dose exhibiting the higher uncertainty (20).…”
Section: Discussionmentioning
confidence: 99%
“…Jumpeno, Ardyanti, and Afham [6] showed that no fading occurred on the re-reading at the 31 st day after Cs-137 gamma irradiation. Kadir et al [7] reported that the OSL dosimeter showed a better response to photon of various energies compared to the TLD-100 and the TLD-100H.…”
Section: Introduction mentioning
confidence: 99%